Characterization of a successful school leadership experience in a chilean school (Praxis Educativa, 2024)
The present article describes the main qualities and strategies of the school´s Principal leadership in a school in theregion of Ñuble, Chile. The analysis of the case study is carried out by using a qualitative methodology with aninterpretative approach, by means of the conduction and analysis of 12 interviews and 1 focus group to differentactors of the educational community. Based on the methodology proposed by the International Successful SchoolPrincipalship Project (ISSPP), we address the challenges posed in the context of school management, thecontributions of the school management team, the integration of students coming from different social and culturalbackgrounds, and the raising of achievement levels in the school. The study concludes that the qualities andstrategies that characterize the school leadership evidence a successful leadership, as demonstrated by the integrationof the three types of leadership: transformational, distributed, and pedagogical.
Keywords: Education; Educational Managment; Teaching Style